Borders and population growth: Evidence from a century of border regime changes on the Austrian-Czech border - Lucie Coufalová; Fanny H. Dellinger; Peter Huber; Stepan Mikula (Masaryk University, Faculty of Economics and Administration, 2024)
We analyze the impacts of three major unexpected border regime changes that occurred during the course of 20th century on population growth along the Austrian-Czech border. Using historical municipal-level census data reaching back to 1880, we find no effects of the dissolution of the Austro-Hungarian Empire (1919) but strong and oppositely signed effects of the drawing (1948) and the fall (1989) of the Iron Curtain in both countries. Our findings indicate that border regimes affect population growth via economic as well as non-economic mechanisms.
Keywords: N94; R12; R23; J11; 330; Population growth; border regions; economic geography